Narratologie und Mittelalterliches Erzählen : Autor, Erzähler, Perspektive, Zeit und Raum. - Contzen, Eva von (Mittelalter. Perspektiven Mediävistischer Forschung. Beihefte Ser., 2018)
This new series, launched by the Medievalists' Society in 2014, provides a forum for exceptional, topically focused anthologies and conference volumes as well as medievalist monographs. The journal accepts submissions in all disciplines represented by the Society, including Byzantine studies, Latin philology, modern language philologies, history, and theology.